The Role of Artificial Intelligence in Building the Research Competence of Future Doctors of Philosophy - Татарнікова, Анжелика Анатоліївна; Татарнікова, А. А.; Tatarnikova, Anzhelyka A.; Oliinyk, Iryna; Bulavina, Olena; Romanenko, Tetiana; Smirnov, Anton (My University, 2024)
The aim of the article is to arrange and analyse the possibilities of using artificial intelligence (AI) in the development of research competence of future doctors of philosophy (PhDs). The research employed the method of a pedagogical controlled experiment, the method of expert evaluations, and questionnaire survey. The obtained data were analysed through the Student’s t-test and the correlation analysis. Validity and reliability were determined using Cronbach’s alpha. The conducted questionnaire survey gave grounds to study the level of the research competence of future PhDs at the beginning and at the end of the experiment. The study included control and experimental groups, as well as expert evaluation. At the initial stage of the study, certain differences were found between the control group (CG) and experimental group (EG) in terms of research competence. Later, the experimental group showed significant growth in all components of competence, which emphasizes the positive impact of using artificial intelligence in the educational process. The results of the correlation analysis confirm the relationship between the components of research competence in both groups. The results of the study confirm the positive impact of the use of artificial intelligence on the level of research competence of future PhDs.
The Role of Artificial Intelligence in Building the Research Competence of Future Doctors of Philosophy / I. Oliinyk, O. Bulavina, T. Romanenko, A. Tatarnikova, A. Smirnov // Revista de la Universidad del Zulia. – 2024. – Vol. 15, No. 43. – P. 377-396. Режим доступу: DOI: https://doi.org/10.46925//rdluz.43.22
Keywords: Innovation; educational environment; higher education; educational component; skill